ANTARA ADAT DAN SYARIAT (Studi Tentang Tradisi Mandi Safar di Tasik Nambus, Riau, ditinjau dari Perspektif Islam) - Khoiri Khoiri (Islam Futura, 2017)
This research paper is aimed to analyze the tradition of Safar Bathing in Lake Nambus according to the Islamic perspective. This is a field research conducted at Tanjung Darul village, Tebing Tinggi Sub-District, Meranti Islands Regency, Riau Province. The research found that Safar Bathing is not stated in the Nash (Quran and Hadist). One additional reference claimed by the local residents in preserving this tradition is that of Sheikh Syafruddin argument in his book entitled "Ta'liqah", saying that on the night of last Wednesday of Month Shafar in Islamic calendar, Allah revealed 12,000 kinds of misfortunes. Therefore, to avoid this, he wrote seven verses of Al-Qu'ran, drank and bathed with the intention to gain favor and blessings from God. There are some values that can be learned even from Safar Bathing tradition as a form of enriching and preserving indigenous custom. The villagers claimed that it has indirectly popularized Darul Tanjung Takzim as a tourist destination, strengthened the kinship and friendship with others and respected their local leaders and authorities as they once did.